An open-label, first-in-human, single agent, dose escalation study for the evaluation of safety and efficacy of SAR442085 in patients with relapsed or refractory multiple myeloma - Kapoor, Prashant; Nathwani, Nitya; Jelinek, Tomas; Pour, Ludek; Perrot, Aurore; Dimopoulos, Meletios-Athanasios; Huang, Shang-Yi; Spicka, Ivan; Chhabra, Saurabh; Lichtman, Eben; Mateos, Maria-Victoria; Kanagavel, Dheepak; et al. (European journal of haematology, 2024)
OBJECTIVES: Cluster of differentiation 38 (CD38) is a key target on multiple myeloma (MM) cells. This multi-centre, Phase 1, single-agent study (NCT04000282) investigated SAR442085, a novel fragment crystallisable (Fc)-modified anti-CD38 monoclonal antibody (mAb), with enhanced affinity towards Fc-gamma receptor on effector cells in patients with relapsed and/or refractory (RR) MM. METHODS: This study comprised two parts: Part-A (dose-escalation involving anti-CD38 mAb pre-treated and naïve patients) and Part-B (dose expansion). Primary endpoints were maximum tolerated dose and recommended Phase 2 dose (RP2D). RESULTS: Thirty-seven heavily pre-treated patients were treated in Part A. Part-B (dose-expansion) was not studied. Seven dose-limiting toxicities were reported at DL3, DL5, DL6, and DL7. RP2D was determined to be 5-7·5 mg/kg. Most common treatment-emergent adverse events were infusion-related reactions in 70·3% (26/37) patients. Grade ≥3 thrombocytopenia was reported in 48·6% (18/37). Overall response rate was 70% in anti-CD38 mAb naïve and 4% in anti-CD38 pre-treated patients, with a median progression-free survival of 7·62 (95%CI: 2·858; not calculable) months and 2·79 (95%CI: 1·150; 4·172) months and, respectively. CONCLUSIONS: The efficacy of SAR442085 was promising in anti-CD38 mAb naïve patients but did not extend to the larger cohort of anti-CD38 mAb pre-treated patients. This observation, along with transient high-grade thrombocytopenia, could potentially limit its clinical use.
Keywords: recidiva; Humans; lidé středního věku; antigeny CD38; Multiple Myeloma; maximální tolerovaná dávka; Female; Aged; Antibodies, Monoclonal; dospělí; výsledek terapie; senioři; lidé; humanizované monoklonální protilátky; chemorezistence; mnohočetný myelom; Adult; Antibodies, Monoclonal, Humanized; ženské pohlaví; Male; Middle Aged; Treatment Outcome; Aged, 80 and over; monoklonální protilátky; Recurrence; Maximum Tolerated Dose; senioři nad 80 let; ADP-ribosyl Cyclase 1; mužské pohlaví; Drug Resistance, Neoplasm